Isolation, identification, and monoclonal antibody development of largemouth bass virus - Yinghui Qin; Yinghui Qin; Yinghui Qin; Yinghui Qin; Haixiang Liu; Haixiang Liu; Haixiang Liu; Haixiang Liu; Shuangshuang Mao; Shuangshuang Mao; Shuangshuang Mao; Shuangshuang Mao; et al. (Frontiers in Marine Science, 2024)
Largemouth bass virus (LMBV) poses a significant threat to largemouth bass farming, leading to substantial economic losses. In December 2022, massive largemouth bass juveniles died at a fish farm in the city of Xinxiang, China. Through a series of experiments, we conclusively identified LMBV as the causative pathogen. The affected fish displayed anorexia, lethargy, and hemorrhage at the pectoral and caudal fin base. No parasites or pathogenic bacteria were detected on the body surface or gills, or isolated from the diseased fish. Severe hemorrhage, lymphocyte infiltration, and extensive necrosis were observed in the liver, spleen, intestine, and stomach of the moribund fish. The tissue homogenate from the diseased fish induced epithelioma papulosum cyprini cells (EPC) cell death, while no such effects were observed in grouper spleen (GS) cells. Sequence similarity analysis of the major capsid protein (MCP) indicated the virus shared 100% similarity with the LMBV-FS2021 strain, placing it within the Ranavirus genus. Transmission electron microscopy (TEM) observations revealed plenty of hexagonal virions accumulated in the cytoplasm of infected EPC cells. Artificial infection demonstrated that LMBV-XX01 was highly fatal to Micropterus salmoides juveniles, with an LD50 of 103.081 TCID50/fish. RT-qPCR detection confirmed that LMBV appeared in all sampled tissues of the challenged largemouth bass, with significantly higher viral loads detected in the liver and heart compared to other tissues. Additionally, we successfully obtained a highly purified recombinant MCP of LMBV and developed two strains of monoclonal antibodies targeting MCP of LMBV-XX01. Overall, our findings provide valuable materials and insights for the design of prevention strategies and the development of detection methods for LMBV.